The letters of Minerva Mirabal and Manolo Tavárez : love and resistance in the time of Trujillo - Tavárez Mirabal, Minou, 1956-; Mirabal, Minerva, 1926-1960; Tavárez, Manolo, 1931-1963 (University of Florida Press, 2022)
"This volume presents a translation and critical edition of the letters between Dominican revolutionaries Minerva Mirabal Reyes and Manolo Tavárez Justo, which tell an intimate story of life and love under the brutal dictatorship of Rafael Trujillo"--